2009
DOI: 10.1111/j.1468-3083.2008.02937.x
|View full text |Cite
|
Sign up to set email alerts
|

Proliferation, DNA repair and apoptosis in androgenetic alopecia

Abstract: The frontal bald area of patients with androgenetic alopecia has lower proliferation rate that result in follicular miniaturization. There is increased DNA damage that would be beyond the capacity of cells to repair in advanced cases. An alternative pathway would take place in order to eliminate the damaged cells through apoptosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
18
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 33 publications
1
18
0
Order By: Relevance
“…altered degree of proliferation or increased apoptosis could contribute to its pathogenesis. Domyati et al (2009) reported that the frontal (bald) area of patients with androgenetic alopecia has lower proliferation rate that result in follicular miniaturization. There is increased DNA damage that would be beyond the capacity of cells to repair in advanced cases.…”
Section: Discussionmentioning
confidence: 98%
“…altered degree of proliferation or increased apoptosis could contribute to its pathogenesis. Domyati et al (2009) reported that the frontal (bald) area of patients with androgenetic alopecia has lower proliferation rate that result in follicular miniaturization. There is increased DNA damage that would be beyond the capacity of cells to repair in advanced cases.…”
Section: Discussionmentioning
confidence: 98%
“…Thus, the abnormalities in the hair follicles of androgenetic alopecia are consistent with the purported pathophysiologic mechanisms of the condition, implying miniaturization (atrophy or lower depth) of the hair follicle with the predominant involvement of the frontal region. Hair follicle shrinkage with a progressive decrease in the proportion during the mature (anagen) stage was previously linked to a decreased proliferation rate of follicular keratinocytes 14 . Whether the primary cause is vascular dysfunction or local deficits in follicular trophic factors is currently unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular epidemiologic studies have identified associations between polymorphisms in genes involved in DNA-repair pathways and increased risk of various types of cancers, including lung cancer (16 -21). However, when DNA damage is extensive and beyond the capacity of cells to repair, cell replacement through apoptosis may be a preferred alternative to DNA repair (22). So, there exists the possibility that high expression of DNA-repair genes may coincide with resistance to apoptosis on cellular stress like unrepairable DNA damage, therefore contributing to cancer risk.…”
Section: Discussionmentioning
confidence: 99%